2020
DOI: 10.1111/jonm.12936
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the structured handover interventions between nurses in improving patient safety outcomes

Abstract: Nursing handovers, or handoffs, entail the process of transferring and accepting both the responsibility for the care of a patient and patient-specific information. This conveyance of patient data ensures the continuity and safety of the patient care in inpatient setting (The Joint Commission Center for Healthcare, 2014). However, when a misalignment of expectations occurs between the sender of information and the receiver, serious communication failures follow during the handover (The Joint Commission, 2017).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 48 publications
(66 reference statements)
2
45
0
1
Order By: Relevance
“…This quality improvement project has observed that more thorough handovers are occurring since the introduction of the structured ISBAR principles. Similar observations have been made by others 9,10 .…”
Section: Figuresupporting
confidence: 92%
“…This quality improvement project has observed that more thorough handovers are occurring since the introduction of the structured ISBAR principles. Similar observations have been made by others 9,10 .…”
Section: Figuresupporting
confidence: 92%
“…15 Structured and standardized communication handover tools are essential for increasing patient safety in the process of transferring a patient and delivering patient-specific information to the receiving nurse. 28 Communication tools were reported from all countries in this study; however, variations existed in the tools that were used. The most common tool was SBAR (used in three countries) or modified versions of SBAR, ISBAR, 29 and iSoBAR 30 in two and one country, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During handover, team members inspect patients' treatment plans and reorganize the nursing diagnoses [9]. Handover requires comprehensive judgment and communication about the clinical situation related to a patient's disease, thereby directly affecting patient safety.…”
Section: Introductionmentioning
confidence: 99%